Delovanje, ekosistemska vloga in vpliv naravnih motenj na gozdove s poudarkom na vetrolomih in namnožitvah podlubnikov – pregled - Matevž Konjar; Matija Klopčič (Acta Silvae et Ligni)
Natural disturbances represent one of the main management and scientific challenges faced by the forestry sector. Their role is increasing and changing with the growing impact of climate change. This review paper aims to provide a concise and up-to-date overview of scientific findings related to the role and functioning of natural disturbances in forest ecosystems, as well as their significance for forest ecosystem management and the sustainable provision of all forest functions. The article includes a review of recent research efforts and the evolving understanding of the function and role of natural disturbances. Additionally, it provides an overview of research results on various types of disturbances, with a particular focus on windthrows and barkbeetle outbreaks.